Proposals for the implementation to the processing of discrete signals with multi-level correlation function - Смирнов, Алексей Анатольевич (Ukrainian Information Security Research Journal, 2012)
Algebraic approach to study the formation of large ensembles of discrete signals with multi-level correlation function, which is based on the section of circular orbits of group codes. The number and value of sidelobe levels of the correlation function generated sequences, and power band signals are determined by remote and structural properties of polynomial rings over finite fields. Develop proposals for the hardware implementation of devices forming discrete signals with multi-function correlation.